Planting coffee and take care of forest: A case study on coffee cultivation in the forest carried out among people of Palintang, Highland of Bandung, West Java, Indonesia - BUDIAWATI SUPANGKAT ISKANDAR; JOHAN ISKANDAR; RUHYAT PARTASASMITA; RAHMAN LATIF ALFIAN (Biodiversitas Journal of Biological Diversity, 2018)
Iskandar BS, Iskandar J, Partasasmita R, Alfian RL. 2018. Planting coffee and take care of forest: A case study on coffee cultivation in the forest carried out among people of Palintang, Highland of Bandung, West Java, Indonesia. Biodiversitas 19: 2183-2195. People of Palintang hamlet of highland of Bandung, West Java have interacted with the forest ecosystem for a long time. In the past, initially, they cultivated forest by practicing swidden farming system (ngahuma) based on the traditional ecological knowledge which strongly embedded with local culture. During the Dutch colonial, some people of Palintang involved as the laborer of various activities of the culture system in the forest. After Indonesian independence, Palintang people have participated as laborers in various activities in the mixed-cropping (tumpangsari) program of the Forestry Service (Dinas Kehutan) and later on the State Forestry Corporation (Perhutani). In 1983, the tumpangsari program was formally prohibited because of its potency to cause environmental destructions, but some people of Palintang have continuously planted vegetables in the forest to get household income. Although the cultivation of vegetables in the forest provided some economic benefits, however, some forest destruction and environmental destructions, including soil erosion, landslide, pesticide pollution have not been inevitable. In 2005 Perhutani launched the management of forest resources together with the community (PHBM=Pengelolaan Sumber Daya Hutan Bersama Masyarakat), mainly by introducing Arabica coffee (Coffea arabica L) to be planted in the pine (Pinus merkusii Jungh) forest to replace the farming of vegetables in the forest. This paper elucidates the historical process of introduction of Arabica coffee in the pine forest of Palintang through the PHBM program of Perhutani. The method used in this study was qualitative with descriptive analysis. Some techniques, namely observation, semi-structured interview, and participant observation were applied in this study. The result of the study showed that the introduction of coffee had been adopted by rural people of Palintang through a long time process with learning by doing. It was revealed that several factors caused the residents accepting coffee plants to be cultivated on forest land, i.e., coffee plants were only once planted in the past in their area, and the area is suitable for coffee cultivation. Besides, coffee has been considered to be planted and give economic benefits; and was initially planted in combination with annual crops, including vegetables, so that before the coffee is produced, the rural people can still produce annual agricultural products such as vegetable crops. However, when the coffee started to produce, time allocation, labor, and capital were more emphasized on the cultivation of coffee instead of vegetable crops; thus, cultivation of vegetables is gradually reduced and even stopped. The forest ecosystem of Palintang can be utilized and maintained by the rural community as indicated by their perception of the forest ecosystem. Thus, people of Palintang have increased awareness that they want to protect forest areas after their coffee cultivation in the forest area provides economic benefits to them.